3096 Estimation of the Prevalence of Cesarean Delivery for the Extremely Preterm Fetus in Breech Presentation. (27th March 2019) - Dangel, Alissa; Breeze, Janis L; Huggins, Gordon; House, Michael; Kolandaivelu, Kumaran
Abstract : OBJECTIVES/SPECIFIC AIMS: Cesarean delivery is typically performed in the extremely preterm period (23 to 28 weeks) when the fetus is in breech presentation to avoid the potential risk of head entrapment by an insufficiently dilated cervix during a vaginal delivery. Assessment of the prevalence of extremely preterm breech cesarean delivery would help to appropriately guide future clinical interventions designed to increase the feasibility of vaginal delivery for this sub-group of patients. METHODS/STUDY POPULATION: We performed a cross-sectional study of the 2106 U.S. National Vital Statistics birth certificate database to estimate the prevalence of cesarean deliveries performed during the period of gestation from 23 to 28 weeks with a fetus in breech presentation. RESULTS/ANTICIPATED RESULTS: An analysis of the total births in the 2016 registry (3, 945, 875) was performed. The gestational age was limited to the target range of 23 0/7 to 27 6/7 weeks. Multiple gestation deliveries were excluded. This yielded 16, 092 births of which 4, 849 were noted to have breech presentation. The proportion of cesarean deliveries performed for singleton breech fetuses at this gestational range was 87% (4, 203/4, 849). DISCUSSION/SIGNIFICANCE OF IMPACT: The probability of undergoing a cesarean delivery for an extremely preterm fetus in breech presentation is notably higher (87%) when compared to an overall cesarean delivery rate of 31.9%. Specific interventions to allow for vaginal delivery in this particular sub-group of the obstetric population would be useful to reduce maternal morbidity by increasing vaginal deliveries. Future work will attempt to address innovative solutions to prevent head entrapment by the cervix in this particular population and ultimately avoid cesarean delivery.